2012
DOI: 10.1111/j.1537-2995.2011.03557.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood donors' helping behavior is driven by warm glow: more evidence for the blood donor benevolence hypothesis

Abstract: This paper offers objective behavioral evidence that blood donors' charitable giving and blood donation, compared to non-blood donors, is more strongly motivated by warm glow. This provides additional support for the benevolence hypothesis of blood donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(111 citation statements)
references
References 37 publications
7
104
0
Order By: Relevance
“…This higher non-health philanthropy in opt-in countries should influence donation via the consent process only. In support of this contention there is evidence to suggest that health based philanthropy (for example, blood and potentially organ donation) is not related to non-health based philanthropy [25-27]. However, while both deceased and living donation rates may be viewed as altruistic, living donation is a more definitive altruistic act – it is at a cost to the donor, voluntary, and a benefit to the recipient (there is no cost to the donor for deceased donations) [28].…”
Section: Methodsmentioning
confidence: 99%
“…This higher non-health philanthropy in opt-in countries should influence donation via the consent process only. In support of this contention there is evidence to suggest that health based philanthropy (for example, blood and potentially organ donation) is not related to non-health based philanthropy [25-27]. However, while both deceased and living donation rates may be viewed as altruistic, living donation is a more definitive altruistic act – it is at a cost to the donor, voluntary, and a benefit to the recipient (there is no cost to the donor for deceased donations) [28].…”
Section: Methodsmentioning
confidence: 99%
“…As such, we argue that it is important to assess the role of positive emotions on health behaviors. Health research has demonstrated the role of positive emotions on helping-based health behaviors, such as blood (Ferguson, Taylor, Keatley, Flynn, & Lawrence, 2012) and organ donation (O'Carroll, Foster, McGeechan, Sandford, & Ferguson, 2011). However, relative to research on negative emotions there is relatively little research assessing the role of positive emotions on other forms of health behaviors (for exceptions, see Mack et al, 2015;Onwezen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While a number of mechanisms (e.g., reciprocity, kin selection) have been suggested to explain cooperation [1], these do not explain cooperation between anonymous strangers where the possibility for reciprocity is absent, such as in lab based one-shot economic games or blood donation [2][3].To account for cooperation in these contexts researchers have focused on the role of intuitive and emotional processes [2], [4]. One line of research has extended the dual systems framework of system 1 (fast, intuitive, automatic, effortless, emotional) and system 2 (slow, reflective, effortful, proactive and unemotional: [5]) to cooperation [6].…”
Section: Introductionmentioning
confidence: 99%